Theoretical study and experimental verification on a passive control system with isolators and dampers for NPPs. (15th November 2022) - Feng, Yixin; Liu, Wenguang; Xu, Hao; Zhang, Qiang
Abstract: A hybrid passive control system named damped isolated structural system (DISO system) for nuclear power plant structures (NPPs) with double containments is proposed in this paper, in which the outer containment is non-isolated and the inner containment and equipment are isolated with connecting damper installed between two containments. Firstly, a connected single degree of freedom (CSDOF) model was proposed. Subsequently, the vibration characteristics and parametric correlation analysis of proposed systems based on CSDOF model were analyzed. The acceleration and dimensionless displacement variances were derived. The optimal value is related to structural parameters, such as the mass ratio η, ratio of natural vibration frequency γ and structural damping ratio ξ i ξ o . Through data fitting and calibration, the closed-form expression of the optimal parameter κ opt is provided. The accuracy of the expression is verified by numerical simulation. Finally, a shaking table experimental study on the scale model was conducted to verify the theoretical results. The optimal damping parameter in the experimental study was calculated by the fitting formula ( κ opt ). The results show that with optimal parameter, the acceleration and displacement responses of DISO system are both lower than traditional isolated structures (ISO system). The shaking table test results are well consistent with that of theoretical investigation conclusions. Highlights: DISO system composite of non-isolated, isolated structures and connecting dampers. The two containments are connected by dampers to dissipate more seismic energy. The optimal damping parameter can be calculated by the simplified expression provided. Both acceleration and displacement responses are reduced with optimal parameters.